Modern Clinical Diagnosis of Vitamin D Deficiency in Women Undergoing Menopause - qizi, Nuftilloyeva Marjona Jabbor; Furkatovna, Amanova Madina (American Journal of Bioscience and Clinical Integrity, 2025)
Research objective: To assess the effect of cholecalciferol on the severity of climacteric manifestations and the dynamics of cytokine status in women receiving phytoestrogen therapy. Materials and methods. 303 women aged 46 to 56 years were examined. Of these, 229 women had symptoms of climacteric syndrome (CS). In the first stage of the study, clinical symptoms, 25 (OH) D levels, and cytokine profiles were assessed in women with CS (n = 229). Control data were the results of examination of women of similar age, but without symptoms of CS (control group, n = 73). In the second stage, the dynamics of clinical and immunological indicators in two groups of women with CS were studied. The first group (comparison group, n = 57) consisted of patients who received therapy with a phytoestrogen preparation for 6 months. The second group (main, n = 57) included women who, in addition to a similar 6-month course of phytoestrogens, were prescribed cholecalciferol using saturation schemes determined by the initial level of 25 (OH) D in the blood serum. During the course of treatment, the severity of clinical manifestations of CS was assessed, as well as the level of 25 (OH) D, interleukins IL-1β, IL-6, IL-8 and tumor necrosis factor α. After a 6-month course of therapy, 55 women in the comparison group and 50 patients in the main group were re-examined. Results. Climacteric syndrome is characterized by increased serum IL-6 (p = 0.042) and IL-8 (p = 0.036) concentrations and is more often observed in women with vitamin D deficiency (81.1% vs. 68.5%; p = 0.018). The inclusion of cholecalciferol in the treatment regimen led to a significant decrease in anxiety and panic attacks, headache, somatic symptoms, the overall severity of climacteric syndrome according to the Green scale, as well as a significant decrease in IL-6 levels after 6 months of complex therapy. When analyzing the level of IL-8, a significant decrease was found only when phytoestrogens were taken in combination with cholecalciferol. The combination of phytoestrogens with cholecalciferol also provided a significant increase in serum 25(OH)D: from 17.77 [13.58; 24.76] ng/ml to 35.47 [31.49; 43.59] ng/mL (p < 0.001). Conclusion: The results obtained indicate that there is a favorable clinical and immunological effect of vitamin D intake in women with climacteric syndrome.